Appraisal of the difference between the mesiodistal diameters of deciduous incisors and molars and permanent teeth (2023)
Aim: Difference in tooth size between deciduous and permanent teeth can resolve space problems during development of the dentition. Aim: To determine the difference in size between deciduous and permanent teeth in the anterior and posterior areas of the mouth in a group of school-age children from Medellin, Colombia. Materials and methods Design: this longitudinal prospective, descriptive investigation was carried out in 139 skeletal Class I dental stone casts from schoolage children from Medellin. Patients were followed annually from 6 to 12 years of age. The final sample consisted of 53 children (35 girls and 18 boys). Leeway space and the incisor liability were determined. Results: A higher positive leeway space was found in the mandible than in the maxilla (3.622 mm and 1.556 mm, respectively). Incisor liability was negatively higher in the maxilla than in the mandible (-7.884mm and -5.386mm, respectively). Six patients showed a negative leeway space between -1.582 mm and -3.184 mm for the mandible and the maxilla, respectively. No statistical significant differences were found by gender; girls showed higher leeway space and incisor liability than boys. Conclusion Normal values for one ethnic group should not be considered normal for another and each group must be treated according to its own characteristics.